Autonomous versus controlled motivation on career indecision: the mediating effect of career exploration - Paixão, Olímpio (2021)
Effective career decision-making outcomes may depend on the type of motivation underlying career development. The purpose of this study was to analyze how autonomous and controlled motivation predict exploration behaviors and career indecision and in which degree the effect of motivation on indecision is mediated by career exploration (environmental exploration, self-exploration, intended-systematic exploration and amount of information), among a group of high-school students (10th, 11th, and 12th grades, N = 523, M = 16.40). An integrative model was tested using path analysis to test direct and indirect effects and model fit (AMOS 20.0). The final model showed good fit to the data. Three indirect effects were found significant, being self-exploration, and amount of information presented as mediators. Our results highlight the importance to design career interventions not only focusing on promoting exploration behaviors but also on creating purposeful planning, based on students' reasons underlying their involvement in the career decision-making process.